Efficient upgrading of polyolefin plastics into C5–C12 gasoline alkanes over a Pt/W/Beta catalyst. Issue 2 (8th December 2021) - Sun, Mengya; Zhu, Lijun; Liu, Wang; Zhao, Xinpeng; Zhang, Yanfei; Luo, Hu; Miao, Gai; Li, Shenggang; Yin, Shu; Kong, Lingzhao
Abstract : A Pt/W/Beta catalyst allows for an excellent yield (63.6 wt%) of C5–C12 gasoline alkanes along with a narrow carbon number distribution and abundant mono-branched isomers under mild conditions. Abstract : A Pt/W/Beta catalyst was developed for direct and efficient hydrogenolysis of low density polyethylene (LDPE) into C5 –C12 gasoline alkanes with a high yield of 63.6 wt% (yield of C1 –C13 light alkanes is 94.0 wt%) at 250 °C and 3.0 MPa H2 within 1.0 h. The obtained gasoline alkanes have a narrow carbon number distribution and contain abundant mono-branched isomers, which were attributed to well-dispersed Pt species and proximity of the cooperating active sites, especially the moderate acidity upon the introduction of 0.5 wt% tungsten species. The catalyst was also applicable to hydrogenolysis of light low density polyethylene (LLDPE), high density polyethylene (HDPE) and polypropylene (PP) to obtain the valuable gasoline alkanes (C5 –C12 ) in high yield (50.8–73.5 wt%). The C–C bond cleavage of plastics over the Pt/W/Beta catalyst was found to occur through medium to long-chain hydrocarbons ( n -C x, x > 13) based on experiments performed using docosane ( n -C22 alkane) as the model feedstock.